2002
DOI: 10.1046/j.1365-2141.2002.03357.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of autoimmune lymphoproliferative syndrome with an antimalarial drug: preliminary results of a clinical cohort study and molecular observations

Abstract: Autoimmune lymphoproliferative syndrome (ALPS) is a paediatric disease characterized by lymphoproliferation and autoimmunity. Most patients are known to carry heterozygous mutations of the TNFRSF6 gene leading to diminished Fas-mediated apoptosis and failure of activated lymphocytes to undergo apoptosis. A subgroup of patients without the TNFRSF6 gene mutation has similar defective apoptosis and clinical features. No effective treatment has been reported so far. Glucocorticoids, intravenous immunoglobulin and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 43 publications
4
27
1
2
Order By: Relevance
“…Studies in children with ALPS have demonstrated a correlation between a decrease in DNTs and lymphoproliferation with improvement in autoimmune manifestations. 10,37 MRL-lpr mice are also phenotypically and genotypically similar to humans with ALPS. These mice develop more significant autoantibodies.…”
Section: Discussionmentioning
confidence: 95%
“…Studies in children with ALPS have demonstrated a correlation between a decrease in DNTs and lymphoproliferation with improvement in autoimmune manifestations. 10,37 MRL-lpr mice are also phenotypically and genotypically similar to humans with ALPS. These mice develop more significant autoantibodies.…”
Section: Discussionmentioning
confidence: 95%
“…The impact of treatment in reducing the IFN-␥-specific response in tuberculosis has been described previously (1,9,15) and suggests that such tests could be used for monitoring patient response to treatment (1). This pattern may be due to a reduction in antigen load originating from parasitic cysts or to a direct effect of pyrimethamine and sulfonamide on activated lymphocytes through activation of the mitochondrial apoptotic pathway (22). A large discrepancy in drug levels observed in babies (5) may explain why this phenomenon is not observed in all infants.…”
Section: Discussionmentioning
confidence: 99%
“…It is used in the treatment of infections caused by protozoan parasites, such as Toxoplasma gondii and Plasmodium falciparum (11). In addition to its antiprotozoal effects, pyrimethamine may exert immunomodulating activities, including the induction of peripheral blood lymphocyte apoptosis (12)(13)(14)(15). We showed that this drug induces apoptosis of activated lymphocytes via a mechanism that brings into play the upstream caspases (16).…”
Section: Introductionmentioning
confidence: 94%